Financial freedom a proven path to all the money you will ever need - Sabatier, Grant (Avery an imprint of Penguin Random House, 2020)
In 2010, 24-year old Grant Sabatier woke up to find he had $2.26 in his bank account. Five years later, he had a net worth of over $1.25 million, and CNBC began calling him "the Millennial Millionaire." By age 30, he had reached financial independence. Along the way he uncovered that most of the accepted wisdom about money, work, and retirement is either incorrect, incomplete, or so old-school it's obsolete. Financial Freedom is a step-by-step path to make more money in less time, so you have more time for the things you love. It challenges the accepted narrative of spending decades working a traditional 9 to 5 job, pinching pennies, and finally earning the right to retirement at age 65, and instead offers readers an alternative: forget everything you've ever learned about money so that you can actually live the life you want.